Phosphorylation of Coagulation Factor XI by a Casein Kinase Released by Activated Human Platelets Increases Its Susceptibility to Activation by Factor XIIa and Thrombin - Ekdahl, Kristina Nilsson; Elgue, Graciela; Nilsson, Bo (Thrombosis and Haemostasis, 1999)
Previous studies suggest that activated platelets facilitate the cleavage of factor XI by both factor XIIa and thrombin. Extracellular phosphorylation is a mechanism by which the function of plasma proteins can be regulated. Phosphorylation is mediated by a casein kinase which is released by activated platelets concomitant with large amounts of ATP and Ca2+. The purpose of this study was to investigate if factor XI is phosphorylated by a platelet casein kinase and whether phosphorylation may affect its activation properties. It was shown that supernatants from platelets which contain platelet casein kinase phosphorylated factor XI. By Western blot analysis it was shown that phosphorylation of factor XI substantially increased its susceptibility to cleavage by factor XIIa, and, to a lesser extent, by thrombin. The generated factor XIa was functionally active in that it cleaved the chromogenic substrate S2366, and in that factor XIa-antithrombin and thrombin-antithrombin complexes were generated when phosphorylated factor XI was added to blood plasma. The present study indicates that platelet-mediated phosphorylation of factor XI enhances the cleavage of factor XI into XIa and that the generated XIa possesses functional activity. Phosphorylation of factor XI might be an essential regulatory mechanism by which platelets mediate amplification of the coagulation cascade.